2015
DOI: 10.31729/jnma.2766
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Children Receiving General Anaesthesia with Laryngeal Mask Airway Insertion

Abstract: Introduction: Perioperative adverse events are more common in children compared to adult population. Reporting an adverse event proves effective in identifying problems and helps in prevention and early management. Our objective was to identify the types, incidence, and the time of occurrence of perioperative adverse event. We also aimed to find out whether the occurrence of the types of adverse events differs in children below and above five years. Methods: This was a prospective study in 242, ASA Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…43 Most studies demonstrated reporting bias with possible underreporting. Seven studies reported succinylcholine doses that varied significantly: 0.1 mg/kg (n = 2), 44 0.25 mg/ kg (n = 1), 45 0.5 mg/kg (n = 45), 46,47 and 1 mg/kg (n = 8). [48][49][50] Studies were Oxford Center for Evidence-based Medicine levels 2 through 4 (Supplemental Digital Content 5, http://links.lww.com/ALN/B802).…”
Section: E Airway Rescuementioning
confidence: 99%
“…43 Most studies demonstrated reporting bias with possible underreporting. Seven studies reported succinylcholine doses that varied significantly: 0.1 mg/kg (n = 2), 44 0.25 mg/ kg (n = 1), 45 0.5 mg/kg (n = 45), 46,47 and 1 mg/kg (n = 8). [48][49][50] Studies were Oxford Center for Evidence-based Medicine levels 2 through 4 (Supplemental Digital Content 5, http://links.lww.com/ALN/B802).…”
Section: E Airway Rescuementioning
confidence: 99%
“…Na literatura, os EA cirúrgicos prevalentes incluem a infecção de sítio cirúrgico, hemorragia, hematoma, deiscência, hipóxia e vômito, (18,19) portanto, diferentes dos evidenciados neste estudo, principalmente pelo fato de neste terem sido incluídos aqui, estritamente os identificados no POI.…”
Section: Discussionunclassified
“…Laringite pós extubação 47 (26) Edema de língua 34 (19) Lesão de comissura labial 29 (16) Perda acesso venoso por obstrução 23 (13) Infiltração de soroterapia 18 (10) Lesão por pressão 15 (9) Lesão por agente térmico 4…”
Section: Discussionunclassified